Factors associated with arterial stiffness in children aged 9-10 years - Milena Santos Batista; José Geraldo Mill; Taisa Sabrina Silva Pereira; Carolina Dadalto Rocha Fernandes; Maria del Carmen Bisi Molina (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the factors associated with stiffness of the great arteries in prepubertal children. METHODS This study with convenience sample of 231 schoolchildren aged 9-10 years enrolled in public and private schools in Vitória, ES, Southeastern Brazil, in 2010-2011. Anthropometric and hemodynamic data, blood pressure, and pulse wave velocity in the carotid-femoral segment were obtained. Data on current and previous health conditions were obtained by questionnaire and notes on the child's health card. Multiple linear regression was applied to identify the partial and total contribution of the factors in determining the pulse wave velocity values. RESULTS Among the students, 50.2% were female and 55.4% were 10 years old. Among those classified in the last tertile of pulse wave velocity, 60.0% were overweight, with higher mean blood pressure, waist circumference, and waist-to-height ratio. Birth weight was not associated with pulse wave velocity. After multiple linear regression analysis, body mass index (BMI) and diastolic blood pressure remained in the model. CONCLUSIONS BMI was the most important factor in determining arterial stiffness in children aged 9-10 years.